Evaluation of caprine eimeriasis in four districts of the department of Ica, Peru - Terrones V., Ruth (2020)
This study aimed to estimate the prevalence of eimerias in creole goats from four districts of the department of Ica, Peru, as well as to identify the species of eimerias present and to determine the frequency according to the variables origin, age group and sex. Faecal samples (n=728) were collected between July and August 2017. Samples were processed using the qualitative flotation technique with Sheather's solution and quantitative by the modified McMaster method. The species were identified by measuring sporulated oocysts and by morphological characteristics. The prevalence of eimerias was 99.2%, with no significant differences due to age, sex and origin. The average parasite load was 2158 opg, considered as low load. Eight species of eimerias were identified in goats, E. caprina, E. caprovina, E. ninakohlyakimovae, E. arloingi, E. apsheronica, E. jolchijevi, E. alijevi and E. christenseni, being the highest frequency of E. caprovina, E. caprina and E. ninakohlyakimovae (32, 26 and 23% respectively).